Perancangan Aplikasi Ujian Online Pada Masa Pandemi Persiapan Ujian Nasional - suheri (Jurnal Nasional Teknologi Komputer, 2022)
This research was conducted to analyze and design a website which is a technology that is very influential on educational science during the current pandemic, so we need a technology that can support the course of learning and exams. One of them is about the technology of Exam Preparation Applications Using Web-Based Randomized Methods at SMA Negeri 1 Pantai Cermin. The exam itself is an activity that is carried out regularly to measure the achievement of student competencies after completing one or more basic competencies. The research method used consists of several stages of research, namely data collection, system analysis and software design. The data collection method used is observation and literature study. System analysis and design method used is Rapid Application Development (RAD) using Unified Modeling Language (UML) and user interface system design. The application is made on two sides, namely the admin application and the user application. The programming language used for software development is PHP and the server uses MySQL as the database. The result of this research is an online exam website-based application for preparation for the national exam and uses a random method that can later be used by teachers and students. The application of this application can provide convenience for teachers and students in the process of working on computerized exam practice questions and can immediately see exam results quickly.